Effect of Coastal Waves on Hydrodynamics in One-Inlet Coastal Nador Lagoon, Morocco - Jeyar Mohammed; Elmiloud Chaabelasri; Najim Salhi (Modelling and Simulation in Engineering)
Nador lagoon is a coastal system connected to the sea through a narrow and shallow inlet; understanding its hydraulic performance is required for its design and operation. This paper investigates the hydrodynamic impacts of the whole lagoon due to tidal waves using a numerical approach. In this study we use a two-dimensional, depth-averaged hydrodynamic model based on so-called shallow water equations solved within triangular mesh by a developed efficient finite volume method. The method was calibrated and validated against observed data and applied to analyze and predict water levels, tidal currents, and wind effects within the lagoon. Two typical idealized scenarios were investigated: tide only and tide with wind forcing. The predicted sea surface elevations and current speeds have been presented during a typical tidal period and show correct physics in different scenarios.